2023
DOI: 10.1136/bmjgh-2023-012045
|View full text |Cite
|
Sign up to set email alerts
|

Conflicting interests, institutional fragmentation and opportunity structures: an analysis of political institutions and the health taxes regime in Pakistan

Zafar Mirza,
Daud Munir

Abstract: Pakistan is the world’s fifth most populous country, with large segments of its population at risk from non-communicable diseases caused by consumption of harmful products, including tobacco and sugar-sweetened beverages. Even though evidence exists that increased taxes on harmful products leads to consumption reductions as well as increased revenues, Pakistan’s health taxes remain low. We seek to understand the reasons for the deficient health tax regime. Much of the existing literature emphasises industry ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Mirza et al analysed political institutions and the health taxes regime in Pakistan and identified two key aspects of the country’s political institutions resisting change 33. The first barrier to health tax policy were structural issues such as federalism, intraelite conflict, interagency coordination and intra-agency fragmentation in the design and functioning of key institutions 33.…”
Section: Lessons From Individual Case Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Mirza et al analysed political institutions and the health taxes regime in Pakistan and identified two key aspects of the country’s political institutions resisting change 33. The first barrier to health tax policy were structural issues such as federalism, intraelite conflict, interagency coordination and intra-agency fragmentation in the design and functioning of key institutions 33.…”
Section: Lessons From Individual Case Studiesmentioning
confidence: 99%
“…Mirza et al analysed political institutions and the health taxes regime in Pakistan and identified two key aspects of the country’s political institutions resisting change 33. The first barrier to health tax policy were structural issues such as federalism, intraelite conflict, interagency coordination and intra-agency fragmentation in the design and functioning of key institutions 33. The other significant barrier to effective health tax policy was the entrenchment of industry interests within government institutions, exploiting these structural issues and taking advantage of gaps in the governance of conflicts of interest 33.…”
Section: Lessons From Individual Case Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“… 22 , 48 , 49 Our qualitative data indicates that the lack of political will partly stems from politicians’ motivations to support the growth of the domestic pharmaceutical industry and is influenced by industry lobbying against limitations on marketing or proliferation of active companies. These findings are consistent with a recent analysis in Pakistan highlighting the “entrenchment of industry interests within governmental institutions.” 50 …”
Section: Discussionmentioning
confidence: 99%